Development and application of microsatellite markers within transcription factors in flare tree peony (Paeonia rockii) based on next-generation and single-molecule long-read RNA-seq - Na LIU; Fang-yun CHENG; Xin GUO; Yuan ZHONG (Journal of Integrative Agriculture, 2021)
Tree peonies native to China are a precious crop with ornamental, medicinal and edible oil properties, of which flare tree peony (Paeonia rockii) is one of the most significant germplasms in Paeonia. The development and application of expressed sequence tag-simple sequence repeat (EST-SSR) markers are very valuable for genetic and breeding applications, but EST-SSR resources for the genus Paeonia are still limited. In this study, we first reported the development of SSRs within transcription factors (TFs) in P. rockii based on next-generation sequencing (NGS) and single-molecule long-read sequencing (SMLRS). A total of 166 EST-SSRs containing six nucleotide repeat types were identified from 959 candidate TFs associated with yield, with an average of one SSR per 5.83 unigenes. In total, 102 (61.45%) pairs of primers produced amplification products in the two RNA-seq cultivars. Among them, 58 (56.86%) pairs of primers from 18 gene families (AP2, bHLH, HSF, etc.) were identified to be polymorphic both in the parents of a linkage mapping population and in eight randomly selected accessions of P. rockii. Further, the 58 EST-SSRs indicated a high level of informativeness with PIC values ranging from 0.32 to 0.91 (mean 0.70) after assessment in 37 tree peony accessions. Transferability studies indicated that the amplification ratio of the 58 pairs of primers ranged from 89.66 to 100% across seven species of Paeonia. In addition, a genetic relationship study was performed in 62 accessions. Cluster analysis using the neighbour-joining (NJ) tree demonstrated that major clusters corresponded to the known pedigree trees. Taken together, these newly developed EST-SSRs have a potential use in the conservation of tree peony germplasm and marker-assisted selection (MAS) breeding.